Socio-Economic Status of Marine Fishermen in Two Fishing Villages of Orissa - S., Balasubramanian; Bihari, Bankey; Mohan, Braj (Fishery Technology, 2025)
The socio-economic status of fishermen in two marine fishing villages of Orissa State viz., Pentakota and Belinoliasahi were measured using a Socio-economic Status Index (SESI) developed in the study. It was seen that the mean SESI scores of respondents in these two villages (57.53%) had differed significantly at 1% level. Of the nine regression co-efficients calculated between the SES scores and independent variables, the regression co-efficient of two variables viz., knowledge about technological practices and sources of information used were found to be positive and significant in Pentakota village and the R2 (73.38%) was highly significant. But in Belinoliasahi, the R2 (28.30%) was not significant. The results also revealed that the fishermen had favourable attitude towards the motorisation of fishing crafts (71.60% and 81.56%) in both the villages.